2022
DOI: 10.3390/microorganisms10091840
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Diversity of Pectobacterium spp. on Potato in Serbia

Abstract: Pectobacterium is a diverse genus which comprises of multiple destructive bacterial species which cause soft rot/blackleg/wilt disease complex in a wide variety of crops by employing high levels of virulence factors. During the 2018, 2019 and 2020 potato growing seasons, numerous outbreaks of bacterial wilt, stem blackleg and tuber soft rot were recorded, and symptomatic plant samples from ten localities in the Province of Vojvodina (Serbia) were collected and analysed. Bacterial soft-rot pathogens were detect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 80 publications
1
4
0
Order By: Relevance
“…The rep-PCR (BOX-, ERIC-, and REP-PCR) analysis conducted by Alvarado et al [ 49 ] also revealed high genetic variability among P. carotovorum strains isolated from Chinese cabbage in Pernambuco state (north-east Brazil). Based on the rep-PCR with primers for BOX-, ERIC-, and REP-PCR, Loc et al [ 38 ] reached a similar conclusion to the one put forward in this study, positing that Pectobacterium strains of the same species tend to group closely according to their respective taxonomic designations. Considering that authors of several extant studies singled out rep-PCR as discriminative enough to reveal subtle differences between different Pectobacterium spp., as well as those among the same species, as proposed by Zoledowska et al [ 26 ] for P. parmentieri strains from Poland, rep-PCR is a promising technique for the clarification of genetic diversity and discrimination of soft rot-causing Pectobacterium spp.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…The rep-PCR (BOX-, ERIC-, and REP-PCR) analysis conducted by Alvarado et al [ 49 ] also revealed high genetic variability among P. carotovorum strains isolated from Chinese cabbage in Pernambuco state (north-east Brazil). Based on the rep-PCR with primers for BOX-, ERIC-, and REP-PCR, Loc et al [ 38 ] reached a similar conclusion to the one put forward in this study, positing that Pectobacterium strains of the same species tend to group closely according to their respective taxonomic designations. Considering that authors of several extant studies singled out rep-PCR as discriminative enough to reveal subtle differences between different Pectobacterium spp., as well as those among the same species, as proposed by Zoledowska et al [ 26 ] for P. parmentieri strains from Poland, rep-PCR is a promising technique for the clarification of genetic diversity and discrimination of soft rot-causing Pectobacterium spp.…”
Section: Discussionsupporting
confidence: 82%
“…Nonetheless, P. aroidearum , P. brasiliense , P. odoriferum , P. polaris , and P. wasabiae species have also been reported to result in cabbage soft rot in different countries [ 28 , 29 , 30 , 31 , 32 , 33 ]. In Serbia, different Pectobacterium species (i.e., P. atrosepticum , P. brasiliense, P. carotovorum, P. punjabense, P. zantedeschiae, and P. versatile ) have been isolated from broccoli, calla lily, carrot, celery, parsley, potato, squash, and watermelon [ 19 , 20 , 23 , 34 , 35 , 36 , 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…These strains were obtained from a total of 52 samples collected across 38 distinct growing areas. The physiological and biochemical features were used as additional methods for the differentiation of Pectobacterium species (Loc et al., 2022), which aligned with findings from previously characterized Pectobacterium species (Araujo et al., 2021). The strains exhibited typical attributes associated with Pectobacterium taxa, including the formation of cavities on CVP plates, solubility in KOH (rendering them gram negative), facultative anaerobic metabolism, a positive catalase test, and a lack of fluorescence under UV light on KB medium (Charkowski et al., 2020; Czajkowski et al., 2015; Koh et al., 2012).…”
Section: Discussionmentioning
confidence: 65%
“…This atypical classification did not align with the expected characteristics of P. betavasculorum . This uncertainty arises due to the evolving taxonomy and species classification within the Pectobacterium genus (Loc et al., 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In Serbia, different Pectobacterium spp.— P. atrosepticum , P. brasiliense , P. carotovorum , P. odoriferum , P. punjabense , P. zantedeschiae, and P. versatile —have been isolated from various hosts [ 13 , 16 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 ]. Three of these species ( P. carotovorum , P. odoriferum , and P. versatile ) were recently described as causal agents of soft rot in cabbage in this region [ 13 ].…”
Section: Introductionmentioning
confidence: 99%